Compliance With Evidence-Based Processes of Care After Transitions Between Staff Intensivists. Issue 3 (March 2020) - Angriman, Federico; Pinto, Ruxandra; Friedrich, Jan O.; Ferguson, Niall D.; Rubenfeld, Gordon; Amaral, Andre Carlos Kajdacsy-Balla
Abstract : Objectives: We sought to evaluate the impact of transitions of care among staff intensivists on the compliance with evidence-based processes of care. Design: Cohort study using data from the Toronto Intensive Care Observational Registry. Setting: Seven academic ICUs in Toronto, Ontario. Patients: Critically ill mechanically ventilated adult patients. Interventions: We explored the effects of the weekly transition of care among staff intensivists on compliance with three evidence-based processes of care (spontaneous breathing trials, lung-protective ventilation, and neuromuscular blocking agents). Two practices that are less guided by evidence (early discontinuation of antibiotics and extubation attempts) served as positive controls. We conducted the analysis using generalized estimating equations to account for clustering at the patient level. Measurements and Main Results: The cohort consisted of 10, 570 patients admitted between June 2014 and August 2018. Compliance varied for each practice (63.6%, 42.5%, and 21.1% for lung-protective ventilation, spontaneous breathing trials, and neuromuscular blockade, respectively). There was no effect of transitions of care on compliance with spontaneous breathing trials (odds ratio, 1.00; 95% CI, 0.95–1.07), lung-protective ventilation (odds ratio, 1.07, 95% CI, 0.90–1.26), or neuromuscular blockade use (odds ratio, 0.95; 95% CI, 0.75–1.20). However, early antibiotic discontinuation was more likely (odds ratio, 1.23; 95% CI, 1.06–1.42) and extubation attempts were less frequent (odds ratio, 0.77; 95% CI, 0.65–0.93) after a transition of care. Conclusions: We observed no significant impact of transitions of care between individual staff physicians on evidence-based processes of care for mechanically ventilated adult patients. However, transitions were associated with a lower likelihood of extubation and higher odds of earlier discontinuation of antibiotics. Abstract : Supplemental Digital Content is available in the text.